Opera and Choral Performance in Mykhailo Krechko’s Work: ДО 95-РІЧЧЯ ВІД ДНЯ НАРОДЖЕННЯ - Maslennikova, Anzhela (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The article considers some aspects of opera and choral performance on the example of analysis of the theatrical period of creativity of one of the prominent figures of Ukrainian choral culture, founder of the choir of the State Children’s Musical Theater — People’s Artist of Ukraine, Professor Mykhailo Krechko (1925–1996). M. Krechko as the first chief choirmaster of the theater built his individual principles of work and theatrical traditions inherent in such a unique opera choir. SCMT is the second in the world and the only professional opera and ballet theater in Ukraine for children and youth). The established traditions and peculiarities of the choir’s work in SCMT are analyzed, based on the repertoire of the newly created Theater and the genre range of performances of choir artists (opera, ballet, musical, cantata and oratorio works, a cappella music performance). Formulation of the problem in general. The relevance of the chosen subject is due to the lack of basic scientific research into the life and work of the famous Ukrainian choral conductor M. Krechko. This is the first comprehensive appeal to the activities of an outstanding master of choral work, active propagandist and collector of folk songs, composer, publicist, teacher and music and public figure, who devoted his entire creative life to the development of national choral culture. A separate task is to study and analyze the basis of the traditions of opera and choral performance initiated by M. Krechko during his work at the State Children’s Musical Theater. Also, it is important to systematically study the methodology and means of educating opera choristers on the example of the work of M. Krechko. Analysis of research and publications to solve the problem. General characteristics of the life and work of Mikhail Krechko are examined in the works of O. Bench-Shokalo, M. Kravchuk, A. Lashchenko, L. Mokanu. The issues of choir and opera choir are analyzed in the works of L. Butenko, O. Letychevska, B. Pokrovsky, K. Pigrov, P. Chesnokov, which explores the functioning of the choir and the nuances of managing this process, as well as the work of specialists in the opera house. The problem of the specifics of M. Krechko’s work with the opera choir was not raised in the scientific literature, which determined the relevance of this article. The research materials of the archive of the “Kyiv Municipal Academic Opera and Ballet Theater for Children and Youth” — programs of performances and concerts, reviews; family archival materials of the Krechko family; publications by M. Krechko and devoted to the work of M. Krechko (booklets, articles in newspapers and magazines, author’s books and reference books). Also, below are a number of personal conclusions of the author of the article while working as a choir artist under the direction of M. Krechko. The purpose of the article is to study the life and work of M. Krechko as an opera choirmaster, his methodology and practical implementation of the multitasking of choir artists in a wide range of synthesis of arts in the opera house. Conclusions and prospects for further exploration in this direction. The article explores for the first time the theme of opera and choral performance in the works of the outstanding Ukrainian choirmaster — People’s Artist of Ukraine, Professor Mykhailo Krechko. The above facts from archival materials and analysis of the maestro’s artistic activity allow to learn more about the master’s contribution to the choral art of Ukraine and its important role in the formation of the vector of development of the State Children’s Musical Theater. Emphasis is placed on the specifics and universalism of the theatrical choir. Summarizing all the above, we can say that the modern creative life of the choir Kyiv Municipal Academic Opera and Ballet Theater for Children and Youth is fundamentally based on the high artistic principles laid down by the founder of the choir — Mykhailo Krechko. The Maestro’s great love for the Theater Choir, which he called his “swan song”, high performing skills and a wide range of genres of repertoire, education of followers and like-minded people, and deep traditions established by the choirmaster are a strong foundation and guide to new artistic victories.